A brief history of western philosophy - Kenny, Anthony (Blackwell Pub., 1998)
In this lucid and masterful work, the eminent scholar Anthony Kenny offers an indispensable resource - the most concise and compelling story of the complete development of philosophy available.Spanning 2,500 years of thought, this superb volume provides essential coverage of the most influential philosophers of the Western world, including Socrates, Plato, Aristotle, Jesus, Augustine, Aquinas, Machiavelli, Descartes, Hobbes, Spinoza, Berkeley, Hume, Rousseau, Kant, Hegel, Marx, Mill, Nietzsche, Darwin, Freud, Frege, Russell, and Wittgenstein, amongst many others.Unrivaled in its authority and range, the book is ideal for anyone with an interest in Western thought.